Flexible parents: joint effects of handicapping and brood size manipulation on female parental care in Nicrophorus vespilloides. (21st March 2018) - Ratz, Tom; Smiseth, Per T.
Abstract: Parental care is highly variable, reflecting that parents make flexible decisions in response to variation in the cost of care to themselves and the benefit to their offspring. Much of the evidence that parents respond to such variation derives from handicapping and brood size manipulations, the separate effects of which are well understood. However, little is known about their joint effects. Here, we fill this gap by conducting a joint handicapping and brood size manipulation in the burying beetle Nicrophorus vespilloides . We handicapped half of the females by attaching a lead weight to their pronotum, leaving the remaining females as controls. We also manipulated brood size by providing each female with 5, 20 or 40 larvae. In contrast to what we predicted, handicapped females spent more time provisioning food than controls. We also found that handicapped females spent more time consuming carrion. Furthermore, handicapped females spent a similar amount of time consuming carrion regardless of brood size, whereas controls spent more time consuming carrion as brood increased. Females spent more time provisioning food towards larger broods, and females were more likely to engage in carrion consumption when caring for larger broods. We conclude that females respond to both handicapping and brood size manipulations, but these responses are largely independent of each other. Overall, our results suggest that handicapping might lead to a higher investment into current reproduction and that it might be associated with compensatory responses that negate the detrimental impact of higher cost of care in handicapped parents.